2012
DOI: 10.1007/s11605-012-1898-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Quality of Life After Pancreatoduodenectomy: A Prospective Study Comparing Preoperative and Postoperative Scores

Abstract: PD has a favorable impact in quality of life as demonstrated by the improvement of most parameters assessed in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…In the present study, social functioning and emotional role restriction improved after surgery following a short decline. This trend was reported previously. A positive effect for mental health over time was observed here.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, social functioning and emotional role restriction improved after surgery following a short decline. This trend was reported previously. A positive effect for mental health over time was observed here.…”
Section: Discussionsupporting
confidence: 92%
“…Patients completed this questionnaire at home after visiting the surgeon and sent it back by mail, or completed it in the waiting room. Follow‐up questionnaires were scheduled for completion during routine visits to the outpatient department at 1, 3, 6 and 12 months after surgery, until loss to follow‐up or death. Patients who remained in hospital were considered unable to complete questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the questionnaires did not reveal any differences in quality of life between the groups. A decline in HRQoL 1 month after PD is expected and has been described previously 34 . There are no studies evaluating quality of life after implementation of FT PD, but a comparison of FT versus traditional management of patients undergoing colorectal surgery showed no difference in EORTC QLQ-C30 scores 35 .…”
Section: Discussionsupporting
confidence: 66%
“…It has been shown that operated patients have a higher quality of life 6 months postoperatively than before surgery [56].…”
Section: Operability Assessmentmentioning
confidence: 99%